Metagenomic characterization of lysine acetyltransferases in human cancer and their association with clinicopathologic features. Issue 5 (24th April 2020) - Jiang, Yuanyuan; Guo, Xuhui; Liu, Lanxin; Rode, Shomita; Wang, Rui; Liu, Hui; Yang, Zeng‐Quan
Abstract: Lysine acetyltransferases (KATs) are a highly diverse group of epigenetic enzymes that play important roles in various cellular processes including transcription, signal transduction, and cellular metabolism. However, our knowledge of the genomic and transcriptomic alterations of KAT genes and their clinical significance in human cancer remains incomplete. We undertook a metagenomic analysis of 37 KATs in more than 10 000 cancer samples across 33 tumor types, focusing on breast cancer. We identified associations among recurrent genetic alteration, gene expression, clinicopathologic features, and patient survival. Loss‐of‐function analysis was carried out to examine which KAT has important roles in growth and viability of breast cancer cells. We identified that a subset of KAT genes, including NAA10, KAT6A, and CREBBP, have high frequencies of genomic amplification or mutation in a spectrum of human cancers. Importantly, we found that 3 KATs, NAA10, ACAT2, and BRD4, were highly expressed in the aggressive basal‐like subtype, and their expression was significantly associated with disease‐free survival. Furthermore, we showed that depletion of NAA10 inhibits basal‐like breast cancer growth in vitro. Our findings provide a strong foundation for further mechanistic research and for developing therapies that target NAA10 or other KATs in human cancer. Abstract : Integrated genomic, transcriptomic, and clinicopathologic data and loss‐of‐function screens in a large cohort of primary tumors and cell lines identified a subset of lysine acetyltransferases (KATs), notably NAA10, that were significantly associated with cancer aggressiveness and poor prognosis. Loss‐of‐function analysis revealed that NAA10 had important roles in promoting cancer cell growth and survival. Our findings provide a strong foundation for further mechanistic research and for developing therapies that target NAA10 or other KATs in human cancer.